(untitled) (ABUJA JOURNAL OF BUSINESS AND MANAGEMENT, 2024)
Conflict is an inevitable part of any organizational setting, especially in complex environments like educational and healthcare institutions. The main objective was to assess conflict management and organizational performance in Jos University Teaching Hospital (JUTH). A descriptive research design was employed, with a population comprising 2808 employees of JUTH. A sample size of 350 respondents was selected using multistage sampling technique. The data used for this study was obtained through a structured and a close-ended questionnaire. The data collected were presented using tables and analyzed with simple percentages, while multiple regression analysis and ANOVA were used to test the hypotheses. The research findings revealed that Negotiation, Conciliation and Arbitration have positive significant impact on quality of graduating students, service delivery and quality of research work in Jos University Teaching Hospital (JUTH). The study concluded that conflict management strategies are pivotal for the attainment and achievement of organizational goals and objectives and if the management is not knowledgeable in conflict resolution strategies, it will affect the performance of organizations negatively but if conflict is constructively managed, it will enhance organizational performance. The study recommended that management of JUTH should develop diverse but appropriate strategies like negotiation in JUTH to enhance employees’ productivity, create group interaction and conciliation activities as well as organize seminars/workshops on organizational conflict management from time to time for the employees.